Job Insecurity and Organizational Citizenship Behavior: A Study of Organizational Identification and Coworker Support. - Weerapaiboon, Wongladda; Akkawanitcha , Chuanchuen; Sangchoey, Thanakrit (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
Nowadays, digital technology plays an important role in the financial services business. Labor forces are replaced by technology and the job roles are reduced. This paper aims to present a model of the influence of job insecurity and organizational identity towards organizational citizenship behavior of employees. According to the literature, the current paper proposes the concept of “organizational identity” as the mediating role of the relationship between job insecurity and organizational citizenship behavior. Moreover, the concept of “coworker support” is presented as the moderator in the relationship between job insecurity and organizational citizenship behavior. This paper concludes that coworker support will buffer the negative relationship between job insecurity and organizational citizenship behavior. Article history: Received 20 February 2020 Revised 11 May 2020 Accepted 14 May 2020 SIMILARITY INDEX = 0.00 %